Increased calcium in neurons in the cerebral cortex and cerebellum is not associated with cell loss in the mdx mouse model of Duchenne muscular dystrophy. Issue 13 (9th September 2015) - Tuckett, Emma; Gosetti, Troy; Hayes, Alan; Rybalka, Emma; Verghese, Elizabeth
Abstract : Duchenne muscular dystrophy (DMD) is a fatal neuromuscular disease resulting from mutation of the X-linked dystrophin gene. In addition to skeletal muscle pathology, cognitive deficits have been identified in patients with DMD. There is a lack of research investigating the pathological mechanisms underlying the neurological deficits apparent in DMD. The current study assessed whether increases in calcium contributed towards neuronal cell loss or histopathological changes in the genetically homologous mdx mouse model of DMD in sections from the cerebral cortex, hippocampus and cerebellum at 24 days, 12 weeks and 9 months of age. Alizarin S staining showed a significant increase in calcium-positive neurons in the mdx cerebral cortex at 24 days and 9 months and the cerebellum at 24 days, 12 weeks and 9 months compared with age-matched controls. However, neuronal cell counts of haemotoxylin and eosin-stained sections showed that altered calcium levels did not lead to neuronal cell loss. A better understanding of how the disruption of calcium regulation affects the function of neurons may explain the neurological deficits apparent in mdx mice and patients with DMD.